(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article begins with a brief description of the dictionary and terminological meaning of the word zakat, as well as the sharia ruling. It also contains a description of the issues of zakat of gold, silver and other precious stones based on Movarounnahr and other fiqh sources.